2012
DOI: 10.1097/ico.0b013e31822f3c18
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Herpes Simplex Keratitis Presenting as Peripheral Ulcerative Keratitis

Abstract: Bilateral herpetic keratitis presenting as PUK is an extremely rare manifestation of herpetic disease. PUK can pose a diagnostic dilemma in cases with immune system dysregulation. Excluding infectious agents is mandatory for appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…A recent study has reported that the levels of inflammatory factors, such as G-CSF, TNF-α, IL-6, and IP-10, are significantly higher in severely ill COVID-19 patients than those in less severely ill patients, indicating that cytokine surge is involved in the pathogenesis of the disease [12]. In infectious immune corneal injuries, bilateral peripheral ulcerative keratitis caused by the herpes simplex virus [19] and bilateral disciform keratitis complicated by adenoviral conjunctivitis [20] due to the induction of inflammatory reactions or immunological responses in the corneal stroma by immune-degrading complexes have also been reported. However, these delayed corneal infiltrations display different clinical signs, and therefore, they are often misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported that the levels of inflammatory factors, such as G-CSF, TNF-α, IL-6, and IP-10, are significantly higher in severely ill COVID-19 patients than those in less severely ill patients, indicating that cytokine surge is involved in the pathogenesis of the disease [12]. In infectious immune corneal injuries, bilateral peripheral ulcerative keratitis caused by the herpes simplex virus [19] and bilateral disciform keratitis complicated by adenoviral conjunctivitis [20] due to the induction of inflammatory reactions or immunological responses in the corneal stroma by immune-degrading complexes have also been reported. However, these delayed corneal infiltrations display different clinical signs, and therefore, they are often misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of Coronavirus Disease 2019 (COVID- 19) in December 2019, the number of infections and deaths has increased exponentially. At the time of this writing, more than 2 million people have been infected with SARS-CoV-2 worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
“…it is characteristically unilateral. 1 Bilateral herpetic keratitis is particularly rare, with a reported incidence of 1% to 10%. [2][3][4] Bilateral involvement may be noted in patients with atopy, measles, graft-versus-host disease, immunodeficiency, and in younger patients.…”
mentioning
confidence: 99%
“…12,13 In some cases, the DNA HSV isolation by PCR has been the only microbiological test that supported the diagnosis of stromal necrosis due to herpetic infection. 14 Other authors suggest that a combination of at least two laboratory tests, such as PCR for HSV-1 DNA, Giemsa stain for multinucleated giant cells, or immunofluorescence assay (IFA) for HSV-1 antigen, could be required to confirm the diagnosis in atypical cases of HSV keratitis. 15 Finally, the invasive but definitive methods to diagnose the infective cause of the stromal lysis in these RA patients would be the immunohistopathology of the corneal biopsy, 16 as was described in 1 of the 2 cases reported by Zaher; electron microscopy was performed and showed clusters of typical herpes virus particle within almost all of the keratocytes.…”
Section: Discussionmentioning
confidence: 99%
“…18 Bilateral HSK is very rarely reported in the literature and bilateral herpetic keratitis presenting as PUK is considered an even rarer manifestation of herpetic disease. 14 The recurrence of some form of ocular HSV occurred in 2 of 5 patients (40%) during follow-up, both having recurrences even during the prophylactic oral regimen considered standard for immunocompetent patients, [19][20][21] one as the typical geographic ulcer pattern after penetrant keratoplasty and the other as stromal necrotizing with positive PCR. Case 2 experienced recurrence with famciclovir 250 mg/day but stopped at 750 mg/day.…”
Section: Discussionmentioning
confidence: 99%